ANALISIS PRAKTIK ASUHAN KEPERAWATAN DENGAN INTERVENSI EXPRESSIVE WRITING THERAPY UNTUK MENGURANGI KECEMASAN PADA IBU POST PARTUM - Savira Ilsa Fahrina (2022)
Anxiety is a feeling that cannot be expressed in words but can be seen from various body gestures. The cause of anxiety is a feeling of guilt as a result of an action that a person does by producing something that is not expected, being afraid of something that happens to oneself can also cause a person to feel anxious. This analysis aims to determine the results of expressive writing therapy on postpartum maternal anxiety. This analysis uses 2 samples of respondents, 1 managed respondent and 1 resume respondent. The results showed that the patients who were given the intervention (managed) were in the no longer anxious category with a total score of 13, while the patients who were not given the intervention (resume) remained in the category of moderate anxiety with a total score of 21. Several things can affect the anxiety scale for caring children including self-confidence and support from family. Then there is an average decrease in postpartum maternal anxiety before and after being given expressive writing therapy.